2014
DOI: 10.1177/1687814020901652
|View full text |Cite
|
Sign up to set email alerts
|

Parameters optimization of two-speed powertrain of electric vehicle based on genetic algorithm

Abstract: Aiming at the shortcomings of only optimizing the gear ratios of two-speed transmission in the optimization process of two-speed powertrain parameters of electric vehicles, the optimization of two-speed powertrain parameters of electric vehicles based on genetic algorithm is proposed. The optimization process is to optimize the main performance parameters of the drive motor and the gear ratios of two-speed transmission. That is, taking the economy and dynamic of the electric vehicle as the fitness function, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Recently, Han et al [17] presented a systematic framework to optimize the gear numbers, gear ratios, and gearshift schedule in the transmission system for EVs considering several driving conditions. In another study, Li et al [18] conducted parameter optimization of both the electric motor and a two-speed transmission system in an EV. Both research groups used the road inclination to set the dynamic performance target and the upper limit of the gear ratios during the optimization process.…”
Section: Ev Transmission Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Han et al [17] presented a systematic framework to optimize the gear numbers, gear ratios, and gearshift schedule in the transmission system for EVs considering several driving conditions. In another study, Li et al [18] conducted parameter optimization of both the electric motor and a two-speed transmission system in an EV. Both research groups used the road inclination to set the dynamic performance target and the upper limit of the gear ratios during the optimization process.…”
Section: Ev Transmission Modelmentioning
confidence: 99%
“…The maximum step ratio is set to 3.4 based on a study conducted by Zhou et al [9]. Now, GR 1max and GR 2min can be estimated by using Equation (18) i.e.,…”
Section: Boundary Conditions and Constraintsmentioning
confidence: 99%
“…Parameters optimization of two-speed powertrain of electric vehicle based on genetic algorithm (GA) is considered in [10]. The different GA for a gearbox optimization (internal combustion engines) is used in the paper [11].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 11 proposed a power train optimization method based on the genetic algorithm, which optimized the drive parameters of the motor while optimizing the transmission ratio, and they formulated dynamic and economical shifting rules. The results showed that when optimizing the transmission ratio and motor drive parameters, a selected performance indicator of the electric vehicle, such as the power, economy, or comprehensive performance, could be improved by formulating a proper shift schedule.…”
Section: Introductionmentioning
confidence: 99%